Orbital alignment and mass segregation in galactic nuclei via vector resonant relaxation. Issue 3 (6th May 2022) - Magnan, Nathan; Fouvry, Jean-Baptiste; Pichon, Christophe; Chavanis, Pierre-Henri
ABSTRACT: Supermassive black holes dominate the gravitational potential in galactic nuclei. In these dense environments, stars follow nearly Keplerian orbits and see their orbital planes relax through the potential fluctuations generated by the stellar cluster itself. For typical astrophysical galactic nuclei, the most likely outcome of this vector resonant relaxation is that the orbital planes of the most massive stars spontaneously self-align within a narrow disc. We present a maximum entropy method to systematically determine this long-term distribution of orientations and use it for a wide range of stellar orbital parameters and initial conditions. The heaviest stellar objects are found to live within a thin equatorial disc. The thickness of this disk depends on the stars' initial mass function, and on the geometry of the initial cluster. This work highlights a possible (indirect) novel method to constrain the distribution of intermediate mass black holes in galactic nuclei.